Exposure to tobacco secondhand smoke and its associated factors among non-smoking adults in smoking-restricted and non-restricted areas: findings from a nationwide study in Malaysia - Kuang, Hock Lim; Chien, Huey Teh; Nik Mohamed, Mohamad Haniki; Pan, Sayan; Miaw, Yn Ling; Mohd Yusoff, Muhammad Fadhli; Hassan, Noraryana; Baharom, Nizam; Dawam, Netty Darwina; Ismail, Norliana; Mohd Ghazali, Sumarni; Kee, Chee Cheong; et al. (BMJ Publishing Group, 2018)
Objectives Secondhand smoke (SHS) has been associated with increased morbidity and mortality. Therefore, the aims of the paper are to assess SHS exposure among non-smoking adults in Malaysia attending various smoking-restricted and non-restricted public areas according to the Control of Tobacco Product Regulations (CTPR) as well as its relationship with various sociodemographic variables.